2012 16th IEEE Mediterranean Electrotechnical Conference 2012
DOI: 10.1109/melcon.2012.6196456
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous flight control for an RC helicopter

Abstract: This paper presents an autopilot system for a Radio Controlled (RC) helicopter, in a simulation environment. The controller is designed using Fuzzy Logic in order to achieve simplicity and cost effectiveness. The system controls the helicopter from takeoff to landing, allowing the craft to reach any position and hover stably with a defined yaw attitude at the request of the user. The Fuzzy Inference Systems (FIS) in use were able to allow for these operations with more than satisfactory results, even in simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In the research of RC helicopter control we found that the researches published in literature about the RC helicopter control design aspect are presented by [4][5]. Reference [4] presented the autopilot system for a Radio Control helicopter in simulation environment. The controller is designed by using Fuzzy Logic in order to achieve simplicity and cost effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…In the research of RC helicopter control we found that the researches published in literature about the RC helicopter control design aspect are presented by [4][5]. Reference [4] presented the autopilot system for a Radio Control helicopter in simulation environment. The controller is designed by using Fuzzy Logic in order to achieve simplicity and cost effectiveness.…”
Section: Introductionmentioning
confidence: 99%